The role of sea spray in air-sea fluxes during Typhoon Molave: a study based on drifting buoy observations - Li, Shuo; Wang, Bin; Deng, Zengan; Dang, Chaoqun; Li, Yawen; Sun, Dongbo; Chen, Zhaohui (Frontiers in Marine Science, 2023)
The exchange of heat and momentum between the ocean and the atmosphere greatly affects the growth of typhoons. Utilizing the meteorological and oceanic variables observed by a Drifting Air-sea Interface Buoy (DrIB) during Typhoon Molave, a new air-sea turbulent fluxes product (referred to as DrIB product) is developed with the consideration of the thermal and dynamic effects of sea spray in the Coupled Ocean Atmosphere Response Experiment algorithm. The performances of two reanalysis products, ERA5 and MERRA2, under typhoon conditions are evaluated by comparing them to the DrIB observations. In particular, the air-sea turbulent fluxes during Typhoon Molave are systematically studied. The averaged heat (momentum) flux of the DrIB product is ~200% (~30%) higher than the reanalysis. However, the reanalysis products have higher latent heat than the DrIB product, because the reanalysis products have lower wind speed, smaller air-sea temperature difference, and drier atmosphere. The sea spray-induced mean heat (momentum) flux increase is ~1% (8%) in normal weather and is ~5% (17%) at the during-typhoon stage. Sea spray amplifies the dominance of wind speed on heat fluxes and weakens the contribution of air-sea temperature and humidity differences to heat fluxes. Sea spray starts to obviously contribute to the heat fluxes at a 10-m wind speed of ~10 m/s, and it non-linearly accelerates the air-sea heat exchange at a 10-m wind speed of ~20 m/s. When the 10-m wind speed is less than 20 m/s, the basic momentum flux (without sea spray effects) at the air-sea interface is roughly one or two orders of magnitude higher than the sea spray-induced momentum flux. Including the sea spray effects, the maximum momentum flux can even double at the 10-m wind speed of ~30 m/s.